Prevalence and social environment of cigarette smoking in Cyprus youth - Christophi, Costas A.; Kolokotroni, Ourania; Alpert, Hillel R.; Warren, Charles W.; Jones, Nathan R.; Demokritou, Philip; Connolly, Gregory N. (My University, 2008)
Background. Tobacco use is the single most preventable cause of morbidity and mortality in humans. Limited data exist regarding the extent of the problem among Cyprus youth. We use the Global Youth Tobacco Survey to assess the prevalence of cigarette smoking among middle and high school students as well as the social environment in which this is taking place. Methods. The survey was conducted by the Cyprus International Institute for the Environment and Public Health in association with Harvard School of Public Health. A two-stage cluster sample design was used to select a representative sample of students from middle and high schools registered with the Republic of Cyprus in 2005-2006. The study questionnaire consisted of 99 questions and participation in the survey was voluntary. Statistical analyses were performed taking into consideration the specific design of the study and the sample weights associated with each completed questionnaire. Results. The prevalence of current smoking, defined as having smoked cigarettes on one or more days of the past 30 days, is 13% among boys and 7% among girls in middle schools, and 36% among boys and 23% among girls in high schools. Furthermore, 16% of middle school students and more than 24% of high school students that had never smoked indicated that they are likely to initiate smoking within the next year. Exposure to environmental tobacco smoke is also very high with 91% of students reporting being exposed to smoke in places outside home. In addition, more than 95% of current smokers reported that they had bought cigarettes in a store during the past month and were not refused cigarettes because of their age. Conclusion. Smoking prevalence among Cyprus middle and high school students is high and there are indications of an increase in the prevalence of smoking among girls over the last few years. Susceptibility rates, exposure to second-hand smoke, and access to and availability of cigarettes to youth are also high and concerning. The present survey indicates that the problem of cigarette smoking among youth in Cyprus is significant and requires collective action immediately. © 2008 Christophi et al; licensee BioMed Central Ltd.
Keywords: Adolescent Behavior; Smoking; Cyprus; health education; sex difference; passive smoking; child behavior